Modern approaches to artificial gene synthesis: aspects of oligonucleotide synthesis, enzymatic assembly, sequence verification and error correction - G. Y. Shevelev; D. V. Pyshnyi (Вавиловский журнал генетики и селекции)
Synthetic biology is a rapidly developing field aimed at engineering of biological systems with predictable properties. Synthetic biology accumulates the achievements of modern biological sciences, programming and computational modeling as well as engineering technologies for creation of biological objects with user-defined properties. Evolution of synthetic biology has been marked by a number of technological developments in each of the mentioned fields. Thus, significant reduction in cost of DNA sequencing has provided an easy access to large amounts of data on the genetic sequences of various organisms, and decreased the price of the DNA sequence synthesis, which, analogous to Moore’s law, resulted in an opportunity to create a lot of potential genes without the time – consuming and labor – intensive traditional methods of molecular biology. Development of system biology has allowed forming a deeper understanding of the functions and relationship of natural biological models, as well as of the computational models describing processes at the cell and system levels. Combination of these factors has created an opportunity for conscious changes of natural biological systems. In this review the modern approaches to oligonucleotide gene assembly synthesis are discussed, including such aspects as protocols for gene assembly, sequence verification, error correction and further applications of synthesized genes.